2019
DOI: 10.2147/jpr.s172733
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning and mindfulness skills training in chronic pain: a systematic review

Abstract: PurposeThe importance of improved physical function as a primary outcome in the treatment of chronic pain is widely accepted. There have been limited attempts to assess the effects mindfulness skills training (MST) has on objective outcomes in chronic pain care.MethodsThis systematic review evaluated published reports of original randomized controlled trials that described physical function outcomes after MST in the chronic pain population and met methodological quality according to a list of predefined criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
1
30
1
Order By: Relevance
“…33,34 Using a commercially available digital monitoring device such as a Fitbit offers the potential to help individuals monitor their step count and reinforce activity goals. 33,43 Finally, our findings highlight the extent of associations within measurement modalities and dissociations across measurement modalities. There were significant and mostly moderate-tostrong correlations across all of the patient-reported measures, regardless of the specific construct they were intended to assess.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…33,34 Using a commercially available digital monitoring device such as a Fitbit offers the potential to help individuals monitor their step count and reinforce activity goals. 33,43 Finally, our findings highlight the extent of associations within measurement modalities and dissociations across measurement modalities. There were significant and mostly moderate-tostrong correlations across all of the patient-reported measures, regardless of the specific construct they were intended to assess.…”
Section: Discussionmentioning
confidence: 62%
“…39,40 We grouped these factors together since cultivating mindfulness and relaxation is an established adaptive coping strategy in the face of pain and difficulty. [41][42][43] The third category consists of socialemotional dysfunction (anxiety, depression social isolation, emotional support), as these constructs are often interrelated and are frequently coupled in relevant literature. [44][45][46]…”
Section: Methodsmentioning
confidence: 99%
“…The emphasis on feasibility markers in preparation for efficacy is an additional strength of the study, which helps ensure the scientific rigor of the next step of the efficacy trial. Second, this study is the first RCT that follows recommendations from recent IMMPACT [ 18 , 19 ] and ICF [ 17 ] criteria to comprehensively assess physical function using objective, performance-based, and self-reported measures in chronic pain trials [ 71 ]. Finally, this study found improvements in physical function [ 71 ], pain coping [ 72 , 73 ], and pain intensity [ 11 , 73 ], which are similar to or larger than those found in other mind-body interventions, suggesting that our mind-body physical activity program shows strong potential for efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to limitations in study design which is reflected in many reviews reporting the low quality of included studies. Typically, systematic reviews reveal a range of limitations such as poor conceptualization of the core focus of the study ( Jackson et al, 2019 ), lack of consensus in measures used ( Banerjee et al, 2018 ), wide range of intervention content ( Elbers et al, 2018 ), methodological bias ( Amatya et al, 2018 ), small sample sizes ( Hilton et al, 2016 ), risk of bias ( Anheyer et al, 2019 ), overestimation of effect ( Niederer and Mueller, 2020 ), and inconsistency in follow-up duration ( Devan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%